Elite forces of India and Pakistan - Conboy, Ken; Colour Plates by Hannon, Paul (London Osprey Publishing Ltd., 1992)
Both India and Pakistan inherited a core of professional, highly trained armed forces after independence in 1947. This volume details the arms, equipment, organization and uniforms of these elite troops of the sub-continent.
Includes Colored Illustrations
Keywords: Special forces (Military science) -- India -- Special forces (Military science) -- Pakistan